The information revolution in Asia - Hachigian, Nina (National Defense Research Institute, RAND, 2003)
This report discusses the information revolution in the Asia-Pacific region and its likely course over the next five to ten years. Key questions addressed in this report include the extent to which the information revolution has taken hold of markets in this region, the political implications of the information revolution for Asian governments, the variations between individual countries, and the prospects for further information-technology-related developments in the region. The authors address two questions about the effect of the information revolution on the economies of the Asia-Pacific region: (1) To what extent do Asian countries and markets use IT, and (2) to what extent do they produce IT software and hardware? The authors determine that Japan, South Korea, Singapore, and Taiwan are today both major users and producers of IT. Australia, Hong Kong, and New Zealand are large users but not producers, whereas Malaysia, the Philippines, and Thailand produce large quantities of technology products but are not big users. In examining the effect of the information revolution on politics and governance in Asia, the authors present a varied picture. IT has contributed to political change in liberal democracies and one-party dominant states alike and will play a large role in any political transitions that occur in wired countries. Although e-government has the potential to usher in significant change in the relationship between government and citizens, most such shifts will be only gradual.